Research note: Representing identity and relationships in information systems - Mike Martin (International Journal of Business Science & Applied Management (IJBSAM), 2007)
This research note is concerned with how identity and of relationship are represented in information systems. It presents a real world example of the problems that can arise in the delivery of social care and explores some thoughts about the application of Peirce's ideas to respond to these issues in the context of case management and record systems.
Keywords: 650; identity; relationships; information systems